Italy and the USA cultural change through language and narrative - Bonsaver, Guido; Carlucci, Alessandro; Reza, Matthew, 1986- (Italian perspectives, 2019)
This collection takes a cross-disciplinary, transnational approach and gathers together essays from a range of subjects including linguistics, film studies, folk music, oral and written narrative, and history, which provide new comparative perspectives on the questions surrounding the mutual influence between Italian and U.S. cultures. The volume also showcases new research -- quantitative, interpretative, and archival -- which contributes to the study of cultural contact. It therefore offers new evidence to answer a question which has long been pivotal in various disciplines and research fields (from historical linguistics to cultural anthropology) -- namely, how and to what extent cultural contact can affect long-term historical change?